Biportal Endoscopic Transforaminal Lumbar Interbody Fusion with Arthroscopy - Kim, Ju-Eun; Choi, Dae-Jung (Clinics in orthopedic surgery, 2018)
Lumbar spine fusion has been widely accepted as a treatment for various spinal pathologies, including the degenerative spinal diseases. Transforaminal interbody fusion (TLIF) using minimally invasive surgery (MIS-TLIF) is well-known for reducing muscle damage. However, the need to use a tubular retractor during MIS-TLIF may contribute to some limitations of instrument handling, and a great deal of difficulty in confirming contralateral decompression and accurate endplate preparation. Several studies in spinal surgery have reported the use of the unilateral biportal endoscopic spinal surgery (technique for decompression or discectomy). The purpose of this study is to describe the process of and technical tips for TLIF using the biportal endoscopic spinal surgery technique. Biportal endoscopic TLIF is similar to MIS-TLIF except that there is no need for a tubular retractor. It is supposed to be another option for alternating open lumbar fusion and MIS fusion in degenerative lumbar disease that needs fusion surgery.